2013
DOI: 10.1002/minf.201300024
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Molecular Basis of Qobc1 Complex Inhibitors Activity to Find Novel Antimalarials Hits

Abstract: Cytochrome bc1 complex is a crucial element in the mitochondrial respiratory chain, being indispensable for the survival of several species of Plasmodia that cause malaria and, therefore, it is a promising target for antimalarial drug development. We report a molecular docking study building on the most recently obtained X-ray structure of the Saccharomyces cerevisiae bc1 complex (PDB code: 3CX5) using several reported inhibitors with experimentally determined IC50 values against the Plasmodium falciparum bc1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 49 publications
1
14
0
Order By: Relevance
“…4. The correlation analysis indicated the inhibition of DNMT1 activity follows a highly dependence with calculated binding scores for these compounds (r= 0.83, p value <0.0001; for binding affinity vs logIC50, r= 0.65, p value <0.0001; for Total score vs logIC50), with correlation coefficients comparable to those reported in other studies for these validations[56,59,60,73] as shown inFig. 4a and Fig.…”
supporting
confidence: 70%
See 2 more Smart Citations
“…4. The correlation analysis indicated the inhibition of DNMT1 activity follows a highly dependence with calculated binding scores for these compounds (r= 0.83, p value <0.0001; for binding affinity vs logIC50, r= 0.65, p value <0.0001; for Total score vs logIC50), with correlation coefficients comparable to those reported in other studies for these validations[56,59,60,73] as shown inFig. 4a and Fig.…”
supporting
confidence: 70%
“…The feasibility of NPs to work as inhibitors of DNMTs was evaluated with two docking programs frequently used for virtual screening, AutoDock Vina [54][55][56] and Surflex-Dock [57]; which are based on different score functions to evaluate the binding mode of a ligand onto a receptor. United/All-atoms force fields with AMBER charges.…”
Section: Molecular Docking With Autodockvina and Surflex-dockmentioning
confidence: 99%
See 1 more Smart Citation
“…Several comparative studies have been published over time, highlighting the strengths and weaknesses of each software tool. For example, AutoDock 4.0 was recently used to discover novel antiplasmodial compounds as potential cytochrome bc 1 inhibitor starting points for medicinal chemistry optimization [95]. For example, AutoDock 4.0 was recently used to discover novel antiplasmodial compounds as potential cytochrome bc 1 inhibitor starting points for medicinal chemistry optimization [95].…”
Section: Examplesmentioning
confidence: 99%
“…Inhibitors of cytochrome bc1 complex may be divided into two types that act on Qi and Qo sites according to the binding site. Some studies suggest that yeast bc1 complex structure could be used as a model for discovering new antimalarial drugs [24,25]. The mutations in the cytochrome b (cob) gene have been found to be the molecular basis of drug resistance [25][26][27][28].…”
mentioning
confidence: 99%